Balinese Adverbial Verbs - Widya Purnawati, Ketut; Artawa, Ketut (International Journal of Psychosocial Rehabilitation, 2020)
The focus of this paper is on adverbial verbs in Balinese. The result of the analysis showed that Balinese adverbial verbs can be classified into manner adverbial verbs, temporal adverbial verbs, frequency adverbial verbs, and directional adverbial verbs. The base forms of the manner adverbial verb are adjectives, demonstratives, numerals, and classifiers. The time adverbial verbs can be formed from time units indicating parts of the day. The base forms of the frequency adverbials can be the time units like day, week, month, and year for a quantifying frequency, whereas complex bases that indicate once, twice, or three times in English are the base forms for a cardinal frequency. Proportional frequencies that can be distinguished into high, middle, and low frequency are formed from words indicating frequency such as „always‟, „rarely‟, etc. Syntactically, the adverbial verb form in Balinese can undergo morphological changes in accordance with the voice of the main verb that the adverbial verb modifies. Thus the adverbial verb can be in objective and agentive voice.